THEORETICAL AND PRACTICAL ASPECTS OF ATTRACTING DIRECT INVESTMENT: METHODS AND MECHANISMS - Navruzov Ikram Abdullaevich (Web of Journals Publishing, 2024)
The article creating a positive investment climate should not be interpreted as a key process in the globalization of the economy, and as a result, the expansion of access to investment resources, which in turn will increase competition among investors. If we want to increase the volume of foreign investment, it is necessary to increase the investment potential of enterprises, regional conditions and conditions to a more acceptable and higher level than others (competitors), as well as to stimulate domestic (national) investment. We need to focus on ensuring that it is holistic.
Keywords: Investment attractiveness, investment potential, investment policy, investment climate, foreign investment, investment potential, recipient, donor, investment attraction mechanism, investment flow.